KETERKAITAN RETURN ON ASSETS (ROA) DAN FIRM SIZE DALAM MEMPENGARUHI PERATAAN LABA PERUSAHAAN - NUGRAHINI KUSUMAWATI (Jurnal Akademika, 2018)
The aimed of this study was to examine the influence of company's characteristics toward income smoothing practice among listed companies at Indonesian Stock Exchange. The factors being examined were return on asset and firm size. Index Eckel is used to determine the income smoothing. The study used 11 companies listed at Indonesia Stock Exchange, in period between 2012-2015. The hypothesis was tested using multiple regression. The first hypothesis was used to examine the influence of return on asset to income smoothing practice. The second hypothesis was used to examine the influence of firm size to income smoothing . The third hypothesis was used to examine the influence of return on asset and firm size to income smoothing .The result of this study indicated that 11 out of 20 companies which were used as samples committed income smoothing . The output of multiple regression showed that return on asset and firm size not having a significant influence to income smoothing. Keyword: return on assets, firm size, income smoothing